Exosomes mediate horizontal transmission of viral pathogens from insect vectors to plant phloem - Chen, Qian; Liu, Yuyan; Ren, Jiping; Zhong, Panpan; Chen, Manni; Jia, Dongsheng; Chen, Hongyan; Wei, Taiyun (eLife, 2021)
Numerous piercing-sucking insects can horizontally transmit viral pathogens together with saliva to plant phloem, but the mechanism remains elusive. Here, we report that an important rice reovirus has hijacked small vesicles, referred to as exosomes, to traverse the apical plasmalemma into saliva-stored cavities in the salivary glands of leafhopper vectors. Thus, virions were horizontally transmitted with exosomes into rice phloem to establish the initial plant infection during vector feeding. The purified exosomes secreted from cultured leafhopper cells were enriched with virions. Silencing the exosomal secretion-related small GTPase Rab27a or treatment with the exosomal biogenesis inhibitor GW4869 strongly prevented viral exosomal release in vivo and in vitro. Furthermore, the specific interaction of the 15-nm-long domain of the viral outer capsid protein with Rab5 induced the packaging of virions in exosomes, ultimately activating the Rab27a-dependent exosomal release pathway. We thus anticipate that exosome-mediated viral horizontal transmission is the conserved strategy hijacked by vector-borne viruses.